Mekar Enterprise - Mumad, Balqis Nuraqilah; Marius, Edward Keith; Arisen, Mohd Azlee Nidzam (2018)
Our executive compensation to study the opportunity and strategic plan in business specifically to SMEs. Through questionnaire and case study we will able to reach the key features regarding conducted study. The key objectives of our executive compensation study to get the level satisfaction of customers. These key are to let customers satisfy regarding food and services provided. Through findings we can obtain valuable information appropriate customers behavior towards food and services which meeting organizational goals. We want the beverages disadvantage will be solve with efficiently and effectively as we produce healthy and cold beverages. Working hard towards this study so that we can get the accurate results and manage to get answer for each question that we provide for the targeted customers who currently live in our market geographical segmentation. Hence, this study or research is very significant for us because it will be the key features and indicators to achieve certain goals and meeting customers with key product that would drive towards demand and profitable.